The Effect of Using Augmented Reality-Based Learning Media on Chemistry Students’ Conceptual Understanding on Molecular Shape - Febrian Solikhin; Dewi Handayani; Salastri Rohiat (Acta Chimica Asiana, 2022)
This study aims to examine the effect of using Augmented Reality-based learning media on students' conceptual understanding of molecular shape material. This research is a quasi-experimental study with a post-test-only design. The class used was class X Mathematics and Natural Sciences in one of the Bengkulu City High Schools, which received molecular shape material, consisting of 1 control class and 1 experimental class. The control class is a class that uses PowerPoint media as usual with 2-dimensional image visualization. In contrast, the experimental class is a class that uses augmented reality-based learning media with 3-dimensional visualization. The instrument used is a post-test instrument referring to conceptual understanding indicators. The results were analyzed using a t-test. The results of the analysis showed that the significance level was 0.002. This result indicates that it is smaller than the significance level, or it can be concluded that there is a significant difference in the average understanding of the concept between the control class and the experimental class.